2020
DOI: 10.1002/masy.201900053
|View full text |Cite
|
Sign up to set email alerts
|

Magnetorheological Elastomer Composites: The Influence of Iron Particle Distribution on the Surface Morphology

Abstract: Iron particles ranging from 50 to 150 µm are incorporated in an elastomer matrix to obtain magnetorheological elastomer (MRE) composites, aiming to investigate their effects on the surface morphology. The isotropic and anisotropic distribution of fillers are estimated in MRE composites. A simulation analysis is carried out to predict the particle distribution in MRE composites, and a correlation between the experimental observation and simulation analysis is established. The volume fraction of 30 vol% is chose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, certain differences exist between these two material groups. The most important difference is that magnetic particles in elastomer composites have a very limited ability to move in the matrix [6][7][8]. The change of their position is in practice possible only through elastic deformation of the matrix solid material.…”
Section: Introductionmentioning
confidence: 99%
“…However, certain differences exist between these two material groups. The most important difference is that magnetic particles in elastomer composites have a very limited ability to move in the matrix [6][7][8]. The change of their position is in practice possible only through elastic deformation of the matrix solid material.…”
Section: Introductionmentioning
confidence: 99%
“…The study discovered that the rheological properties of the material were enhanced after the homogeneous dispersion of the magnetic particles was achieved. Additionally, the 3D images internal structure of the MRE were also investigated, and the simulation result revealed that the distribution of filler particles within the volume, in both isotropic and anisotropic distribution have a significant effect on the properties of MRE [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Filler-matrix adhesion was investigated to verify the quality of the composite. The attachment of iron particles within the elastomer matrix was examined using both microscopy and internal volume of the composite [29].…”
Section: Surface Characterization Using Sem and μCt Techniquementioning
confidence: 99%